2012
DOI: 10.1002/bit.24495
|View full text |Cite
|
Sign up to set email alerts
|

Structured three‐dimensional co‐culture of mesenchymal stem cells with meniscus cells promotes meniscal phenotype without hypertrophy

Abstract: Menisci play a crucial role in weight distribution, load bearing, shock absorption, lubrication, and nutrition of articular cartilage within the knee joint. Damage to the meniscus typically does not heal spontaneously due to its partial avascular nature. Partial or complete meniscectomy is a common clinical treatment of the defective meniscus. However, this procedure ultimately leads to osteoarthritis due to increased mechanical stress to the articular cartilage. Meniscus tissue engineering offers a promising … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
41
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 56 publications
(45 citation statements)
references
References 42 publications
(46 reference statements)
3
41
1
Order By: Relevance
“…In contrast, the same hypertrophic expression in PEG-Peptide scaffold was substantially lower than that in PEG group. This strongly inhibited hypertrophy was striking comparing to previous hMSCs chondrogenic studies using TGFβ [12], in which MSC hypertrophy persists as a consistent hallmark despite strong chondrogenic effect delivered by TGFβ. It suggests that the persistent hMSCs hypertrophy in chondrogenic differentiation could be significantly alleviated by an uncomplicated bioprinted PEG-Peptide system.…”
Section: Accepted Articlementioning
confidence: 53%
See 1 more Smart Citation
“…In contrast, the same hypertrophic expression in PEG-Peptide scaffold was substantially lower than that in PEG group. This strongly inhibited hypertrophy was striking comparing to previous hMSCs chondrogenic studies using TGFβ [12], in which MSC hypertrophy persists as a consistent hallmark despite strong chondrogenic effect delivered by TGFβ. It suggests that the persistent hMSCs hypertrophy in chondrogenic differentiation could be significantly alleviated by an uncomplicated bioprinted PEG-Peptide system.…”
Section: Accepted Articlementioning
confidence: 53%
“…Cells were expanded as previously reported [12,15]. Fifth passage (P5) hMSCs were used in this study.…”
Section: Human Mesenchymal Stem Cell Monolayer Expansionmentioning
confidence: 99%
“…Previous studies have found that the meniscus itself contains a subpopulation of multipotential cells [23,30,36,64], which can be utilized to regenerate tissue. Moreover, the combination of MSCs with native meniscal cells is known to prevent MSC hypertrophy [65,66]. Future work will focus on the interactions between exogenously delivered MSCs and endogenous meniscal cells under the direction of meniscus tissue-specific cues present in mECM hydrogel.…”
Section: Discussionmentioning
confidence: 99%
“…With digital control and high throughput printheads cells, scaffolds, and growth factors can be precisely deposited to the desired twodimensional (2D) and three-dimensional (3D) positions rapidly. Many successful applications have been achieved using this technology in tissue engineering and regenerative medicine [1][2][3][4][5][6][7][8][9] . In this paper, a bioprinting platform was established with a modified Hewlett-Packard (HP) Deskjet 500 thermal inkjet printer and a simultaneous photopolymerization system.…”
Section: Introductionmentioning
confidence: 99%